Are personal budgets a financially sound reform option for the German long-term care insurance? - Arntz, Melanie; Thomsen, Stephan L. (Jahrbücher für Nationalökonomie und Statistik, 2010)
In a long-run social experiment, personal budgets have been tested as an alternative home care program of the German long-term care insurance (LTCI). By granting the monetary value of in kind services in cash, personal budgets are considered to enable customized home care arrangements, thereby avoiding costly nursing home care and thus saving LTCI spending. However, personal budgets also compete with the already existing and less generous cash option of the LTCI. Any transition from the receipt of cash benefits to personal budgets thus challenges the view of personal budgets as a cost savings device, unless personal budgets sufficiently reduce the use of costly nursing home care to balance these extra costs. This paper therefore contrasts the short-term costs of implementing personal budgets with potential cost savings if personal budgets enhance the stability of home care and avoid costly nursing home care. For this purpose, the paper investigates the effects of personal budgets on the duration of home care until moving to a nursing home as well as the perceived stability of home care. Despite a positive effect of personal budgets on the stability of home care, LTCI spending is likely to increase in the short to medium run. In the long run, however, the expected transition to decreasing numbers of cash recipients favors the introduction of personal budgets.